Lenny Cáceres (2022). La transversalidad del género: Espacios y disputas. Lomas de Zamora, Editorial Sudestada, 192 páginas. (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2023)
La transversalidad del género: Espacios y disputas is a work written by Lenny Cáceres, a feminist journalist graduated from the National University of La Pampa. In his work, Cáceres presents a series of articles that from a reflective stance intend to connect individual trajectories and the collective path in a network that allows to bring together the plots of gender. Her approach brings together diverse territorial voices that have been invisibilized and tries to conceive a collective and horizontal voice.